2020
DOI: 10.1101/2020.07.02.20144840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The reproduction number R for COVID-19 in England: Why hasn’t “lockdown” been more effective?

Abstract: The reproduction number R, the average number of people that a single individual with a contagious disease infects, is central to understanding the dynamics of the COVID-19 epidemic. Values greater than one correspond to increasing rates of infection, and values less than one indicate that control measures are being effective. Here, we summarise how changes in the behaviour of individuals alter the value of R. We also use matrix models that correctly recreate distributions of times that individuals spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…To curb an initial rapid increase in COVID-19 cases, the UK entered a nationwide “lockdown” on March 23rd 2020, where people were instructed to stay in their homes except for essential journeys. This generally proved successful, decreasing the R 0 value to approximately 0.81 ( 2 ) during this period. The UK has since begun to ease these lockdown measures, with businesses being allowed to operate and social gatherings permitted subject to certain limitations.…”
Section: Introductionmentioning
confidence: 86%
“…To curb an initial rapid increase in COVID-19 cases, the UK entered a nationwide “lockdown” on March 23rd 2020, where people were instructed to stay in their homes except for essential journeys. This generally proved successful, decreasing the R 0 value to approximately 0.81 ( 2 ) during this period. The UK has since begun to ease these lockdown measures, with businesses being allowed to operate and social gatherings permitted subject to certain limitations.…”
Section: Introductionmentioning
confidence: 86%
“…This was then compared with the sum of new cases over the previous seven-day period. R was estimated using the equation given by Grant (2020) as = Where Y1 and Y2 are the numbers of cases in two consecutive weeks, T is the generation time for the infection (here taken as 5 days) and j is the interval between the midpoints of the periods over which cases are counted (here 7 days). This estimator performs particularly well when R is close to 1 (Grant 2020).…”
Section: Methodsmentioning
confidence: 99%
“…4. Averaging over the infected agents in a given period, we can get a local measure of the infection spreading, a quantity similar to what is in the epidemiology literature known as "R-factor" 46,47 . Our network presentation of the process clearly shows that the R-factor is given by the relative ratio between two successive layers of the Hnods.…”
Section: Fig 2: (Colour Online)mentioning
confidence: 99%
“…Our network presentation of the process clearly shows that the R-factor is given by the relative ratio between two successive layers of the Hnods. Recently, studies have shown that the reproduction rate is a local measure with a limited predictive value, see the discussion and the empirical data analysed in [46][47][48] .…”
Section: Fig 2: (Colour Online)mentioning
confidence: 99%